Mother and Child T Cell Receptor Repertoires: Deep Profiling Study - Putintseva, Ekaterina V.; Britanova, Olga V.; Staroverov, Dmitriy B.; Merzlyak, Ekaterina M.; Turchaninova, Maria A.; Shugay, M; Bolotin, Dmitriy A.; Pogorelyy, Mikhail V.; Mamedov, Ilgar Z.; Bobrynina, Vlasta; Maschan, Mikhail; Lebedev, Yuri B.; et al. (Frontiers in Immunology, 2013)
The relationship between maternal and child immunity has been actively studied in the context of complications during pregnancy, autoimmune diseases, and haploidentical transplantation of hematopoietic stem cells (HSC) and solid organs. Here, we have for the first time used high-throughput Illumina HiSeq sequencing to perform deep quantitative profiling of T-cell receptor (TCR) repertoires for peripheral blood samples of three mothers and their six children. Advanced technology allowed accurate identification of 5х105–2х106 TCR beta clonotypes per individual. We performed comparative analysis of these TCR repertoires with the aim of revealing characteristic features that distinguish related mother-child pairs, such as relative TRBV segment usage frequency and relative overlap of TCR beta CDR3 repertoires. We show that thymic selection essentially and similarly shapes the initial output of the TCR recombination machinery in both related and unrelated pairs, with minor effect from inherited differences. The achieved depth of TCR profiling also allowed us to test the hypothesis that mature T cells transferred across the placenta during pregnancy can expand and persist as functional microchimeric clones in their new host, using characteristic TCR beta CDR3 variants as clonal identifiers.